A versatile mathematical approach for environmental geomechanic modelling based on stress state decomposition - Beneyto, Pablo Alejandro (2015)
Fil: Beneyto, Pablo Alejandro. Universidad Nacional del Nordeste. Facultad de Ingeniería; Argentina.